أسلوب التعليل القرآني وبعض آثاره التعليمية = The principles of Qur’anic argumentation and its educational effects = Prinsip argumentasi al-Quran dan kesan pendidikannya - Elatrash, Radwan Jamal Yousef; Shkukani, Najwa Naif (IIUM Press, International Islamic University Malaysia, 2017)
This study intends to highlight the possible practical impact of the principles of argumentation found in the Qur’an. The study attempts to apply the principles on the actual education process of the scholars and students without limiting it to linguistic studies or theoretical principles. This was done after introducing the principles of reasoning, its tools, its importance, and disclosing the special requirements for the scholars and students in order to be influenced by the latter principles. The work used inductive method to track the works of the scholars on the subject and observe the opinions of the Qur’an-commentators in relation to principles of explanation, verses of argument, and aspects of Qur’anic Inimitability. Analytical method was used to establish the impacts of the Qur’anic arguments; to prove the presence of signs and evidences for the manifestation of the impacts; and to make the continuity of this research possible in all the tools, verses and topics related to the principles of Qur’anic argument. Among those things that enrich this work is that it opens the minds, and pushes it to ponder and study the verses of the Qur’an. For every direction it becomes the starting point for the innovative thinking, and benefit for the new age and its sciences while maintaining the harmony with the principles of creed and the true SharÊ‘ah.